قياس أثر أخلاقيات المهنة على موثوقية نتائج المراجعة الداخلية دراسة تطبيقية على شركة الزاوية لتكرير النفط (Comprehensive Journal of Science, 2025)
The study aimed to measure the impact of professional ethics on the reliability of internal auditing at Al-Zawiya Oil Refining Company, by assessing the effect of independence, integrity, confidentiality, and professional competence on the results of internal auditing.For this purpose, a questionnaire consisting of five sections was designed and distributed to the accountants and auditors at the Al-Zawiya Oil Refining Company, totaling 40 forms. A total of 32 were retrieved and analyzed, representing a retrieval rate of 80%, which indicates the seriousness of the respondents in dealing with the questions.To analyze this data, the Statistical Package for the Social Sciences (SPSS) programs were used to reach a set of results, which confirmed that there is an effect of adherence to professional ethics in enhancing the reliability of internal auditing at Al-Zawiya Oil Refining Company, through integrity, confidentiality, objectivity, and professional competence.